Sprawiedliwość kary z perspektywy ustawowych wskazań jej wymiaru. Rozważania na tle kodeksu karnego - Kania, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The subject of this article concerns the issue of fair sentencing. In order to introduce the essence of a just punishment, the study presents its three models, which have been established with a great contribution of the achievements of criminal law and case law. While highlighting these models, the main focus was placed on the selection of statutory indications that should be helpful in making legitimate judicial decision on penalty measure. The observations suggest that the most convincing viewpoint seems to be the stance in light of which the interpretation of “just punishment” should not be limited to a strict analysis of the provisions under the general directives Art. 53 § 1 of the Polish Penal Code, but must take into account other indications for judicial sentencing. In addition the fact that the subject of this article is very sensitive also leads to the conclusion that any attempts to create a textbook definition of a just punishment are doomed to fail.
Keywords: wyrok sądowy; zasada stopnia winy; sprawiedliwość; słuszna kara; dyrektywa o ogólnej prewencji